2022
DOI: 10.3390/brainsci12050672
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases as Epigenetic Targets for Treating Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a chronic progressive neurodegenerative disease that is increasingly becoming a global threat to the health and life of the elderly worldwide. Although there are some drugs clinically available for treating PD, these treatments can only alleviate the symptoms of PD patients but cannot completely cure the disease. Therefore, exploring other potential mechanisms to develop more effective treatments that can modify the course of PD is still highly desirable. Over the last two decades, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…Butyrate has also been used to differentiate cancer cell-line cultures to a "dopaminergic" phenotype (1 mM dosage) via inhibition of histone deacetylase (HDAC) 35 . Histone acetylation is an epigenetic modification linked with aging and neurodegenerative disease [36][37][38] . Toker et al reported elevated histone acetylation in idiopathic PD patients compared to healthy control patients 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Butyrate has also been used to differentiate cancer cell-line cultures to a "dopaminergic" phenotype (1 mM dosage) via inhibition of histone deacetylase (HDAC) 35 . Histone acetylation is an epigenetic modification linked with aging and neurodegenerative disease [36][37][38] . Toker et al reported elevated histone acetylation in idiopathic PD patients compared to healthy control patients 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Additional evidence points to butyrate potentially providing protection against neurodegeneration via the ability to inhibit histone deacetylates (HDAC) [88][89][90][91] . HDAC inhibitors have been shown to have neuroprotective effects in PD, and other neurodegenerative diseases, by increasing protein acetylation and promoting downstream gene expression and modulation of immune responses [92][93][94] . In models of colitis, HDAC inhibitors have been shown to reduce colitis severity and decrease colonic TNF 95 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) destroys dopaminergic neurons and causes PD-like symptoms, but it also increases the levels of histone H3 acetylation, which are reduced by treatment with levodopa [ 54 ]. High levels of histone H2A, H3, and H4 acetylation are present in dopaminergic neurons in post-mortem PD patients [ 55 ]. Indeed, treatment with HDAC inhibitors reduces α-synuclein neurotoxicity in neuroblastoma cells and in dopaminergic neurons in the α-synuclein transgenic Drosophila model of PD [ 52 , 56 , 57 ].…”
Section: Epigenetics In Neurodegenerative Disordersmentioning
confidence: 99%